Anti-dumping investigation in the EU: how does it work? - Lucy Davis (European Centre for International Political Economy (ECIPE), 2009)
Anti-dumping rules are flexible and open to political bias. This is a concern repeated all over the world. All jurisdictions tailor their anti-dumping laws to WTO rules, but this still leaves a significant amount of discretion as to how decisions are made. In the EU, the lack of transparency in anti-dumping decision making further heightens suspicions that it is not always driven by sound economic assessment. In the past ten years, EU investigating institutions have been biased towards the imposition of measures once a case has been initiated. Whether this is the result of error in the complex calculations required to establish the existence of injurious dumping, or a less benign political bias towards supporting declining domestic industries, is difficult to establish from an outside perspective. What can be achieved is a rigorous examination of the publicly availably information from anti-dumping cases. Investigation reports from the last ten years show repeated laxity in economic analysis and conclusions that are not fully justified by the evidence. When cases are taken to the European Court or the WTO's Dispute Settlement Body (DSB), further errors are exposed. Procedural reform is needed in the investigation process, not least to raise assessment standards and abate suspicions of anti-dumping protectionism.
Keywords: 330; WTO-Recht; Antidumping; EU-Recht; Protektionismus; EU-Staaten